Pengaruh Capital Structure, Liquidity, Firm Size Dan Dividend Policy Terhadap Profitability (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang terdaftar di BEI periode 2017-2019) - Novi Diah Ayu Angelita; Budi Wahono; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study is to test and analyze the profitability of the food and beverage sector manufacturing companies listed on the IDX. To measure these variables, the independent variables that can be used are the variables of capital structure, liquidity, firm size and dividend policy. This research is a type of explanatory research, because this research explains the causal relationship of the independent variables with the dependent variable. The method used is quantitative approach using multiple linear regression analysis using SPSS 16.0 application. The data used is secondary data by collecting data in the form of documentation. In this study, there are a population of 36 companies in the food and beverage sector which are listed on the IDX. Furthermore, purposive sampling is a sampling technique, with a total of 12 samples. From the data management, it shows the results that simultaneously the four independent variables have a significant effect. And partially that the capital structure, liquidity and company size have no effect on profitability, while dividend policy has a significant effect on profitability. Keywords: Capital Structure, Liquidity, Firm Size, Dividend Policy and Profitability